Geriatric oral health care content and barriers to its incorporation in undergraduate nursing curricula: New Zealand survey - Veerasamy, A.; Lyons, K.; Crabtree, I.; Brunton, Paul (2023)
Introduction: An increasingly older population demands major remodeling of our health care system. Older adults are most likely to be affected by the oral-systemic connection due to their impairment in functional capacity and reduced ability to undertake routine oral care. An economic way to improve oral health outcomes in older populations is by involving nurses and caregivers in ensuring the maintenance of oral health for older adults. This study aimed to investigate the present educational content relevant to the oral health of older adults, the oral-systemic connection, and assessment methods in New Zealand nursing education. Methods: A cross-sectional survey was conducted among nursing educators to understand the extent of oral health care education. Quantitative descriptive data were analyzed using SPSS software and qualitative data were analyzed descriptively and presented as themes. Results: The results indicated that the majority of oral health topics were already incorporated into nursing education, however most important topics such as risk factors associated with dental caries, periodontal health, and risk factors are not taught in almost 40% of the schools. The four themes identified in qualitative analyses are “no barrier”, “lack of expertise”, “no space for more content” and oral health content “already included”. Conclusion: Educators reported that oral health topics are already incorporated into New Zealand undergraduate nursing curricula. However, the quantity and quality of oral health content relevant to older adults need to be improved and updated to suit the current oral health care needs of the growing older population.